Dig in! : hands-on soil investigations. - National Science Teachers Association (Arlington, Va. : National Science Teachers Association, 2001)
Contains twelve lessons designed to heighten student awareness of the value of soil through hands-on activities, and includes teaching tips, a glossary, and resources.
"Published with support from the Natural Resources Conservation Service, U.S. Department of Agriculture.".
Includes bibliographical references (p. 123-126).
Professional
Keywords: Creative activities and seat work; Soils -- Study and teaching; Teaching -- Aids and devices; Creative activities; Soils -- Study and teaching; Teaching -- Aids and devices